2015
DOI: 10.1002/pc.23389
|View full text |Cite
|
Sign up to set email alerts
|

Novel polyamide 12/chromium (III) oxide nanoparticles composites: Melting behavior and complex isothermal crystallization kinetics

Abstract: Polymer nanocomposites based on PA12 filled with different loading (0.1−10 wt%) of nanosized (average grain size of about 1−5 nm) chromium(III) oxide were prepared by in situ polymerization, and their mechanical and thermal properties were investigated. A homogeneous dispersion of Cr2O3 nanoparticles in the polyamide matrix was achieved at the level of isolated particles as a result of amphoteric nature of chromium (III) oxide. However, it was found that the tensile modulus and yield stress of the nanocomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…This was shown for the introduction of nanosized oxide F 3 O 4 into polyurethane [7]. We obtained similar results for the preparation of polymer nanocomposites based on PA12 filled with different loading (0.1 -10 wt.%) of nanosized (average grain size of about 1 -5 nm) chromium (III) oxide [8]. It was suggested that the introduction of new fracture mechanisms, rigidity augmentation, and pronounced filler-filler interactions were responsible for the observed behavior instead of filler-polymer interactions [9][10][11][12].…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…This was shown for the introduction of nanosized oxide F 3 O 4 into polyurethane [7]. We obtained similar results for the preparation of polymer nanocomposites based on PA12 filled with different loading (0.1 -10 wt.%) of nanosized (average grain size of about 1 -5 nm) chromium (III) oxide [8]. It was suggested that the introduction of new fracture mechanisms, rigidity augmentation, and pronounced filler-filler interactions were responsible for the observed behavior instead of filler-polymer interactions [9][10][11][12].…”
Section: Introductionsupporting
confidence: 69%
“…However, T g of the composite with 0.1 wt.% of Cr 2 O 3 is very similar (if not identical) to the T g of the pure polymer, but their Young's modulus is similar to moduli for other composites and is much smaller than that of pure PA12 [8], so the decrease in the moduli upon the introduction of the nanoparticles are not only due to a plasticizing effect. The softening of polymer matrix associated with local mobility (β-relaxation) is probably more important.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation